2015
DOI: 10.1039/c5ta03169a
|View full text |Cite
|
Sign up to set email alerts
|

Lead acetate precursor based p-i-n perovskite solar cells with enhanced reproducibility and low hysteresis

Abstract: A low temperature approach for the fabrication of p-i-n perovskite solar cells is presented. Using lead acetate-based precursors, flat and homogeneous CH 3 NH 3 PbI 3 films, compatible with the use of thin organic charge transport layers, can be obtained. The correspondent solar cells showed power conversion efficiency up to 12.5%, with remarkable reproducibility and very low hysteresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 32 publications
2
62
1
Order By: Relevance
“…Consequently, the PSC device showed a high PCE up to 15% and good reproducibility with no obvious hysteresis (Figure 15 c). Furthermore, the Bolink group [ 143 ] investigated the effect of an alternative precursor, lead acetate, on the preparation of a planar PSC device. By substituting lead acetate for lead iodide, they obtained smooth perovskite fi lm that was pinhole-free over [ 53 ] Copyright 2013, Nature Publishing Group.…”
Section: Hysteresis-free Pscmentioning
confidence: 99%
“…Consequently, the PSC device showed a high PCE up to 15% and good reproducibility with no obvious hysteresis (Figure 15 c). Furthermore, the Bolink group [ 143 ] investigated the effect of an alternative precursor, lead acetate, on the preparation of a planar PSC device. By substituting lead acetate for lead iodide, they obtained smooth perovskite fi lm that was pinhole-free over [ 53 ] Copyright 2013, Nature Publishing Group.…”
Section: Hysteresis-free Pscmentioning
confidence: 99%
“…[112][113][114] Based on PbAc 2 lead source, Bolink et al prepared smooth MAPbI 3 perovskite fi lms on the top of PEDOT:PSS. [112][113][114] Based on PbAc 2 lead source, Bolink et al prepared smooth MAPbI 3 perovskite fi lms on the top of PEDOT:PSS.…”
Section: And Maac Refers To Ch 3 Nh 3 (Ch 3 Coo)mentioning
confidence: 99%
“…7 In order to become a veritable rival of silicon, however, several more challenges have to be met, one of which is the development of upscalable deposition processes. [16][17][18][19][20][21][22][23][24][25] It was indeed observed that the presence of even minute amounts of moisture during fabrication can have a detrimental influence on the perovskite's morphology, optical properties and crystallinity, which is obviously reflected in much lower device performance. [9][10][11][12] It is not clear, however, how strict the processing requirements should be in a corresponding production line.…”
Section: Introductionmentioning
confidence: 99%